Assessment of the influence of calcination time and temperature on the com-pressive strength and crystallinity of hydroxyapatite obtained from avian egg-shell (SCIÉNDO INGENIUM, 2025)
The osteoporosis problems affecting our society have motivated researchers to conduct studies in tissue engineering and thus develop biocompatible materials that have characteristics very similar to bone hydroxyapatite. In this study, hydroxyapatite was extracted from chicken eggshells. This material was subjected to tests to determine its degree of crystallinity and compressive strength. To obtain hydroxyapatite, avian eggshells were obtained, which were cleaned, dried, pulverized and sifted, and then calcined at different temperatures (1000°C, 1100°C and 1200°C) and times (3, 3.5 and 4 hours). The crystallinity index was analyzed by X-ray diffraction, and the compressive strength was measured after sintering the hydroxyapatite discs at 150°C. The results show that as the temperature and calcination time increase, the compressive strength also increases, but the opposite occurs with crystallinity. It was concluded that the best combination of properties was found at 1000°C and 4 hours of calcination, obtaining values ​​of 55.19% crystallinity and 0.843 MPa compressive strength.
Keywords: hydroxyapatite; bone tissue; eggshell; biomedical engineering